2019
DOI: 10.1021/acsami.9b14655
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anode Performance and Coking Resistance by In Situ Exsolved Multiple-Twinned Co–Fe Nanoparticles for Solid Oxide Fuel Cells

Abstract: The broad and large-scale application of solid oxide fuel cells (SOFCs) technology hinges significantly on the development of highly active and robust electrode materials. Here, Ni-free anode materials decorated with metal nanoparticles are synthesized by in situ reduction of Fe-doping Sr 2 CoMo 1−x Fe x O 6−δ (x = 0, 0.05, 0.1) double perovskite oxides under a reducing condition at 850 °C. The exsolved nanoparticles from the Sr 2 CoMo 0.95 Fe 0.05 O 6−δ (SCMF0.05) lattice are Co−Fe alloys with rich multipletw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Exsolution of Fe−Co nanoparticles has also been studied extensively usually as anode materials for SOFCs and similar to their Fe−Ni counterparts, they demonstrate a plethora of promising properties such as high activity, stability, coking resistance and sulfur tolerance [6b, c, 7e–g] . A Co‐doped La 0.6 Sr 0.4 FeO 3‐δ (LSF) anode was found to achieve high power density and lower polarization resistance in a SOFC cell as compared to its Mn‐doped counterpart due to the high catalytic activity of the exsolved Fe−Co particles towards hydrogen oxidation and the higher oxygen‐ion conductivity of the newly formed LaSrFeO 4 –La(Sr)Fe(Co)O 3 (the perovskite phase of the Mn‐doped LSF was retained without formation of other phases after reduction) [22] .…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exsolution of Fe−Co nanoparticles has also been studied extensively usually as anode materials for SOFCs and similar to their Fe−Ni counterparts, they demonstrate a plethora of promising properties such as high activity, stability, coking resistance and sulfur tolerance [6b, c, 7e–g] . A Co‐doped La 0.6 Sr 0.4 FeO 3‐δ (LSF) anode was found to achieve high power density and lower polarization resistance in a SOFC cell as compared to its Mn‐doped counterpart due to the high catalytic activity of the exsolved Fe−Co particles towards hydrogen oxidation and the higher oxygen‐ion conductivity of the newly formed LaSrFeO 4 –La(Sr)Fe(Co)O 3 (the perovskite phase of the Mn‐doped LSF was retained without formation of other phases after reduction) [22] .…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
“…The use of bimetallic exsolved systems spans over all kinds of applications including but not limited to electrochemistry (71 %), catalysis (19 %) and membranes (3 %) (Figure 1 b). Among these, electrochemistry [6a–c, 7] is the most common application but there are also a few studies focusing on catalytic applications such as methane conversion, [8] CO oxidation [9] or the water‐gas‐shift reaction [10] . In spite of these exciting developments, to the best of our knowledge, there is no review that summarizes the advances on bimetallic exsolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Barnett has shown that exsolution electrodes on the basis of A-site-deficient and B-site-doped strontium titanates have comparable current densities to NiO/YSZ, and are therefore becoming industrially relevant materials [33]. These results show great promise that cleverly engineered stoichiometry can be synthesized in order to form mixed ionic-electric conductors (MIECs), tailor the electronic properties of the exsolved catalytic nanoparticles through alloying, [33,[35][36][37][38][39] and utilize strain engineering or twinning to enhance catalytic properties [40]. One of the major advantages of SOFCs over room temperature (e.g., PEM) fuel cells is their fuel flexibility and ability to operate using non-precious-metal catalysts.…”
Section: Recent Advancements In Exsolution Electrodesmentioning
confidence: 99%
“…In a SOFC system fueled by hydrocarbon, the anode plays an important role in determining the electrochemical performance and durability of the cell. 7 The anode materials should have a suitable thermal expansion coefficient, high ionic conductivity, high catalytic activity, and strong tolerance to carbon deposition. Conventionally, Ni-based composites, such as Ni-YSZ, which exhibit high catalytic activity and effective current collection, are most commonly used as the anode materials of SOFCs.…”
Section: Introductionmentioning
confidence: 99%
“…A typical SOFC is composed of a dense electrolyte sandwiched between the porous anode and cathode. In a SOFC system fueled by hydrocarbon, the anode plays an important role in determining the electrochemical performance and durability of the cell . The anode materials should have a suitable thermal expansion coefficient, high ionic conductivity, high catalytic activity, and strong tolerance to carbon deposition.…”
Section: Introductionmentioning
confidence: 99%